A New Species-Specific Typing Method for Salivarius Group Streptococci Based on the Dephospho-Coenzyme A Kinase (coaE) Gene Sequencing - Abdelbary, Mohamed M. H.; Wilms, Gerrit; Conrads, Georg (Frontiers in Cellular and Infection Microbiology, 2021)
Viridans streptococci are a group of α-hemolytic streptococcal species. They are mainly commensals, most abundant in the mouth supporting oral health. But they also include important human pathogens such as Streptococcus pneumoniae. Identification and molecular typing of viridans group streptococci are challenging, especially for members of the salivarius group. In this study, we developed a single-locus molecular typing method that is able to differentiate among the highly phylogenetically related members of the salivarius group (S. salivarius, S. vestibularis and S. thermophilus) and might support differentiation in other groups as well. This typing approach is based on the amplification and sequence analysis of the housekeeping gene dephospho-coenzyme A kinase (coaE), a gene with unrecognized taxonomic potential to date. Here, we analysed coaE gene sequences of 154 publicly available genomes and of 30 salivarius group isolates of our own collection that together belong to 20 different gram-positive bacterial (sub) species. Our results revealed that the coaE phylogeny distinguished between streptococcal and non-streptococcal genomes and that coaE gene sequences were species-specific. In contrast to MALDI-TOF MS performance, the coaE typing was able to precisely identify the phylogenetically very closely related members of the salivarius group.